Risk factors for postoperative recurrence of ovarian endometriosis: long-term follow-up of 358 women - Xiao-Yan Li; Xiao-Pei Chao; Jin-Hua Leng; Wen Zhang; Jun-Ji Zhang; Yi Dai; Jing-Hua Shi; Shuang-Zheng Jia; Xiao-Xuan Xu; Si-Kai Chen; Yu-Shi Wu (BMC, 2019)
Abstract Objective To explore the risk factors for the recurrence of endometrioma and the risk factors for the recurrence of endometriosis-related pain after long-term follow-up. Methods This study retrospectively analyzed 358 women with endometriomas who had a minimum of 5-years follow up after laparoscopic endometrioma excision, which was performed at Peking Union Medical College Hospital from January 2009 to April 2013. All women were divided into recurrence group and nonrecurrence group. Analysis was performed with regard to preoperative history, laboratory analysis, findings during surgery, and symptoms during follow-up, including improvement and recurrence. Results The cumulative incidence rates of recurrence from 5 to 10 years after surgery were 15.4, 16.8, 19.3, 22.5, 22.5, and 22.5%, respectively. Significant differences were found between two groups in terms of age at surgery (RR: 0.764, 95% CI: 0.615-0.949, p = 0.015), duration of dysmenorrhea (RR: 1.120, 95% CI: 1.054-1.190, p < 0.001), presence of adenomyosis (RR: 1.629, 95% CI: 1.008-2.630, p = 0.046), CA125 level (RR: 1.856, 95% CI: 1.072-3.214, p = 0.021) and severity of dysmenorrhea. The severity of dysmenorrhea (RR: 1.711, 95% CI: 1.175-2.493, p = 0.005) and postoperative pregnancy (RR: 0.649, 95% CI: 0.460-0.914, p = 0.013) were significantly correlated with endometrioma recurrence in the multivariate analysis. No significant associations were found between the recurrence rate and gravida, parity, body mass index, infertility, leiomyoma presence, the size of ovarian endometrioma, the presence of deep infiltrating endometriosis, disease stage or postoperative medication. Conclusions The severity of dysmenorrhea and postoperative pregnancy were independent risk factors for the recurrence of ovarian endometriomas after surgery during the long-time follow up.